ДОСЛІДЖЕННЯ ФЕНОЛЬНИХ СПОЛУК РОЗХІДНИКА ЗВИЧАЙНОГО (GLECHOMA HEDERACEA L.) - Гарник, М. С. (Фармацевтичний часопис, 2015)
THE INVESTIGATION OF COMPOUNDS PHENOL ORIGIN GROUND IVY (GLECHOMA HEDERACEA L.) M. S. Garnyk NationalPyrogovMemorialMedicalUniversity, Vinnytsia Summary: compounds of phenol origin have been quantified in ground ivy herb, they are hydroxycinnamic acids (4.20-6.47 %), flavonoids (0.77-1.35 %), oxidized phenols (7.75-8.51 %). Flavonoid groups (rutin, hyperozide, apigenin, luteolin, isoquercitrin), coumarines (scopoletin, umbelliferone) hydroxycinnamic acids (rosmarinic, chlorogenic, caffeic, p-coumaric) have been identified by the method of HPLC and their content has been identified. Key words: ground ivy, compounds of phenol origin, spectrophotometry, permanganatometry, high performance liquid chromatography. Introduction. The ability to synthesize and accumulate huge amount of phenolic compounds is a characteristic feature of the representatives of the plant world. Natural phenols exhibit high biological activity. They take part in various physiological processes: respiration, photosynthesis, growth, development and reproduction of plants; some polyphenols protect plants from pathogens and fungal diseases. Medicinal products based on phenolic compounds are widely used as anti-microbial, anti-inflammatory, hemostatic, choleretic, diuretic, hypotensive, tonic, astringent and purgative means. Most of the phenolic compounds of plant origin have low toxicity and do not exhibit side effects. Previous studies found that grass of ground ivy contains a number of phenolic compounds namely: hydroxycinnamic acids, flavonoids, tannins. Therefore the purpose of the study was to determine the quantitative content of phenolic compounds by spectrophotometric method and individual substances by high performance liquid chromatography. Methods. The determination of phenolic compounds recalculated to gallic acid has been performed by spectrophotometric method at a wavelength of 270 nm, the amount of hydroxycinnamic acids recalculated to chlorogenic acid – at a wavelength of 327 nm, the amount of flavonoids recalculated to rutin – at a wavelength of 410 nm; total oxidized amount of phenols has been determined by permanganatometrical titration. To separate the total amount of phenolic compounds into individual components high performance liquid chromatography was used. Results and discussion. The content of phenolic compounds in grass of ground ivy was 3.15-3.41% in the sample number 1 (raw materials harvested in Ternopil region) and 2.98-3.29 % in the sample number 2 (materials harvested in Vinnytsia region), the total content of oxidized phenols is 8.34-8.51 % and 7.75-8.14 %, the amount of flavonoids – 0.87-1.35% and 0.77-1.04 %, the amount hydroxycinnamic acids – 4.20-6.47 % and 4.84-6.36 % respectively for the objects number 1 and number 2. Individual quantitative content of phenolic compounds in the grass of ground ivy was identified by the method of HPLC. Flavonoids (rutin, hyperozide, apigenin, luteolin, isoquercitrin) were identified in the studied objects, as well as coumarins (skopoletyn, umbelliferone), hydroxycinnamic acid (rosmary, chlorogenic, coffeic, p-coumaric), and their quantitative content was determined. Among flavonoid compounds of ground ivy the greatest number falls to rutin – 0.40 and 0.23 % respectively in objects number 1 and 2. As for hydroxycinnamic acid the highest content of rosmarinic acid is observed in the sample number 2 – 1.13 %. The content of chlorogenic acid was also significant and made 0.84 % (№ 1) and 0.81 % (№ 2) in studied objects. Conclusions. 1. Quantitative content of phenolic compounds: total amount of oxidative phenols, total amount of hydroxycinnamic acids, total amount of flavonoids were detected in the studied samples of ground ivy. 2. Quantitative content of flavonoids (rutin – 0.23-0.40 %, hyperozide – 0.17-0.34 %, luteolin – 0.05-0.1% isoquercіtrіn – 0.02-0.03 %, apigenin – 0.06 %), hydroxycinnamic acids (chlorogenic – 0.81-0.84 %, rosmarinic – 0.2-1.13%, coffeic – 0.06 %, p-coumaric – traces) and coumarins (skopoletyn – 0.11-0.12 %, umbelliferonе – 0.02 %) was identified and defined by the method of HPLC.